Peranan Operational Departement dalam Penanganan Kapal MT. Mumbai pada PT. Pelayaran Multi Jaya Samudera Belawan - Robin Berlin Sahputra Halawa; Suparman Suparman; Meriah Kita Deliana N (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The role of the Operational Department in Handling the MT. Mumbai ship at PT. Pelayaran Multi Jaya Samudera Belawan begins when the ship arrives at the port. The shipper sends the documents required in the loading process when the ship arrives, the ship's agency also makes a request for inspection to related agencies such as the Port Health Office, Immigration, Customs and Excise and Belawan Harbor Master The methods used in writing this paper are field research and library research.